2016
DOI: 10.3389/fcell.2016.00057
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Membrane Sterols by Polyene Antifungals Amphotericin B and Natamycin, A 13C MAS NMR Study

Abstract: The molecular action of polyene macrolides with antifungal activity, amphotericin B and natamycin, involves recognition of sterols in membranes. Physicochemical and functional studies have contributed details to understanding the interactions between amphotericin B and ergosterol and, to a lesser extent, with cholesterol. Fewer molecular details are available on interactions between natamycin with sterols. We use solid state 13C MAS NMR to characterize the impact of amphotericin B and natamycin on mixed lipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 36 publications
1
13
0
1
Order By: Relevance
“…To date, no resistance problems associated with echinocandins and amphotericin B have been identified in clinics. However, echinocandin-resistant mutants can be induced easily in vitro (630,631), and hot spots for point mutations inducing the resistance to amphotericin were identified in A. fumigatus after use of natamycin (632)(633)(634) and are starting to be seen in laboratories (635,636). However, resistance to AMB is only anecdotal.…”
Section: Antifungal Drugs and Therapy Antifungal Drugs And Associatedmentioning
confidence: 99%
“…To date, no resistance problems associated with echinocandins and amphotericin B have been identified in clinics. However, echinocandin-resistant mutants can be induced easily in vitro (630,631), and hot spots for point mutations inducing the resistance to amphotericin were identified in A. fumigatus after use of natamycin (632)(633)(634) and are starting to be seen in laboratories (635,636). However, resistance to AMB is only anecdotal.…”
Section: Antifungal Drugs and Therapy Antifungal Drugs And Associatedmentioning
confidence: 99%
“…In this study, the inhibition of fungal growth by natamycin was shown by the performance of FM, which inhibited the growth of most fungal contaminants throughout the study in spite of the medium inhibiting the growth of B. ovis as well. Previous studies have shown that amphotericin B and natamycin have different modes of action even though they both belong to the macrolide polyene class of antibiotics (Ciesielski et al 2016;Lalitha et al 2010). Furthermore, te Welscher et al ( 2008) also reported that natamycin, filipin and nystatin have different mode of action as well.…”
mentioning
confidence: 99%
“…These interactions, added to the action of natamycin on C. albicans and E. coli, lead to a reduction in the final count of these microorganisms. Natamycin has an antimycotic action because of its preference for ergosterol, a sterol present especially in the cell membrane of fungi and little found in bacteria (Ciesielski et al, 2016).…”
Section: Resultsmentioning
confidence: 99%